JUAN MIGUEL BÁKULA AND HIS HISTORICAL-LEGAL LEGACY TO THE PERUVIAN DIPLOMACY A tribute to 10 years of his departure - Peruana de Derecho Internacional, Sociedad (2020)
A tribute to 10 years of his departure